Study of the 2-D copper transport in sandy soil by laboratory scale aquifer model (sand tank) experiment. (1st January 2013) - Saha, Provat K.; Badruzzaman, A.B.M.
In this study, a laboratory scale aquifer model (sand tank) experiment has been carried out to simulate the 2-D transport pattern of copper into the sandy soil. The data collected from the experiment was used for verification of this physical transport experiment by using a flow and transport simulation software (MODFOLW). In case of simulation of laboratory scale aquifer model experiment by using MODFLOW, the trends of predicted copper profiles were similar to the observed profiles. However, model predicts the high aqueous phase copper concentration in most of the cases. Model sensitivity analysis to the partitioning coefficient ( Kd ) shows that the approach of tuning of Kd value can provide a better fit in some trial cases, but it may not be true for all cases. This indicates factors other than Kd are playing a role in this mismatch of data with the model output.